Role of Social Media Influencer’s Credibility in Consumer’s Purchase Decisions - Devi, Suman; Mahapatra, S. N. (The journal of contemporary issues in business and government, 2021)
The use of social media influencers by the companies to promote their products is constantly on the rise since the last decades. Influencers on social media have replaced the celebrities from cinema or sports and now they are the flagbearer of influence. Social media influencers are someone who give character to the consumer’s judgments and shape their attitude regarding a brand or product through their posts in the form of photos, videos and other updates on social media platforms. The present study was conducted to identify the role of social media influencer’s (SMI) credibility in consumer purchase decisions. A structured questionnaire was used to collect the data of 123 respondents from Delhi/NCR. Multiple Regression analysis in SPSS was used to analyze the results. The findings revealed that the attributes of credibility i.e. information value and entertainment value of the branded content shared by SMIs have significant effects on followers.